Coupling between guided modes of two parallel nanofibers. (7th December 2020) - Kien, Fam Le; Ruks, Lewis; Nic Chormaic, Síle; Busch, Thomas
Abstract: We study the coupling between the fundamental guided modes of two identical parallel nanofibers analytically and numerically. We calculate the coefficients of directional coupling, butt coupling, and self coupling as functions of the fiber radius, the light wavelength, and the fiber separation distance. We show that, due to the symmetry of the system, a mode of a nanofiber with the principal quasilinear polarization aligned along the axis joining the nanofibers or the perpendicular axis is coupled only to the mode with the same corresponding principal polarization of the other nanofiber. We find that the effects of the butt coupling and the self coupling on the power transfer are significant when the fiber radius is small, the light wavelength is large, or the fiber separation distance is small. We show that the power transfer coefficient may achieve a local maximum or become zero as the fiber radius, the light wavelength, or the fiber separation distance varies.